The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.915345
|View full text |Cite
|
Sign up to set email alerts
|

Trait mindful awareness predicts inter-brain coupling but not individual brain responses during naturalistic face-to-face interactions

Abstract: In recent years, the possible benefits of mindfulness meditation have sparked much public and academic interest. Mindfulness emphasizes cultivating awareness of our immediate experience and has been associated with compassion, empathy, and various other prosocial traits. However, neurobiological evidence pertaining to the prosocial benefits of mindfulness in social settings is sparse. In this study, we investigate neural correlates of trait mindful awareness during naturalistic dyadic interactions, using both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The scalability of the system offers unprecedented opportunities for studying inter-brain synchrony in large groups. This is an area of Neuroscience research where only very few studies have been performed [ 15 , 29 ] and where it is largely unexplored what are the brain processes that underlie collective and individual behavior in various types of large groups or crowds. Although many aspects of such behavior can be reduced and studied in very small groups or pairs, there are certain conditions that this cannot occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scalability of the system offers unprecedented opportunities for studying inter-brain synchrony in large groups. This is an area of Neuroscience research where only very few studies have been performed [ 15 , 29 ] and where it is largely unexplored what are the brain processes that underlie collective and individual behavior in various types of large groups or crowds. Although many aspects of such behavior can be reduced and studied in very small groups or pairs, there are certain conditions that this cannot occur.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to be able to capture various aspects of induced and intrinsic brain activity in various aspects of human behavior, such as Stress [ 19 , 20 ], Attention [ 21 ], Meditation [ 22 , 23 ], Mindfulness [ 24 , 25 ], Rapid diagnosis of stroke [ 26 ], Drowsiness [ 9 ], Emotion Classification [ 27 ] and Fatigue [ 17 , 28 ]. In a recent study MUSE headsets were used in a hyper-scanning study in an art installation [ 29 ], which was previously using EMOTIV EPOC headsets [ 14 ]. Results seemed to be comparable with both headsets.…”
Section: Introductionmentioning
confidence: 99%
“…The scalability of the system offers unprecedented opportunities for studying inter-brain synchrony in large groups. This is an area of Neuroscience research where only very few studies have been performed (Chen et al, 2022; Dikker et al, 2017) and where it is largely unexplored what are the brain processes that underlie collective and individual behavior in various types of large groups or crowds. Although many aspects of such behavior can be reduced and studied in very small groups or pairs, there are certain conditions that this cannot occur.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to be able various aspects of induced and intrinsic brain activity in various aspects of human behavior, such Stress (Asif et al, 2019; Phutela et al, 2022), Attention(Vortmann et al, 2022), Meditation (Kim et al, 2022; Sharma et al, 2022), Mindfulness (Hawley et al, 2021; Hunkin et al, 2021), Rapid diagnosis of stroke (Wilkinson et al, 2020), Drowsiness (LaRocco et al, 2020), Emotion Classification (Raheel et al, 2019) and Fatigue(Krigolson et al, 2021; Ruyi et al, 2017). In a recent study MUSE headsets were used in a hyper-scanning study in an art installation (Chen et al, 2022), which was previously using EMOTIV EPOC headsets (Dikker et al, 2021). Results seemed to be comparable with both headsets.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, structured mindfulness-based programs have emerged as possible approaches to address a range of clinical and subclinical difficulties, such as stress, chronic pain, anxiety, or recurrent depression (e.g., Brenton-Peters et al, 2021;Piet & Hougaard, 2011;Taylor et al, 2021). In addition, several neuroscientific studies have reported adaptive changes in brain function and structure (i.e., functional and neural plasticity) related to mindfulness training (e.g., Chen et al, 2022;Hölzel et al, 2011;Tang et al, 2012). With regard to the cultivation of mindfulness competence, it should be noted that attentional training skills play a central role in achieving mastery in meditation practices (e.g., Malinowski, 2013).…”
mentioning
confidence: 99%